Assembly of graphene oxide into the hyperbranched frameworks for the fabrication of flexible protein-based films with enhanced conductivities. (1st September 2020) - Jin, Shicun; Li, Kuang; Gao, Qiang; Zhang, Wei; Chen, Hui; Shi, Sheldon Q.; Li, Jianzhang
Abstract: Development of strong and tough biopolymer materials with favorable conductive properties is highly desirable and remains a great challenge in current scientific research. In this study, a novel strategy is designed to prepare a conductive plant protein-based films through the integration of functional graphene oxide (GO) into a hyperbranched network. The process was based on the Fe(III) ion-triggered simultaneous polymerization of dopamine and pyrrole. The incorporation of conductive GO nanosheets with the in situ formed polypyrrole nanoparticles could uniquely act as cross-linking sites to make the nanocomposites highly conductive. As a result, strong sacrificial metal-ligand bonds and covalent bonds would be confined within the network. The toughness and strength of the nanocomposite film increased by 428.5% and 324.1%, respectively. In addition, this hybrid film showed significant improvement in electrical and thermal conductivities owing to the contribution of the highly conductive hyperbranched structures in the polymer matrix. Furthermore, this renewable and biodegradable film had superior water resistance and ultraviolet-barrier performance, which are of great importance to the practical applications. Graphical abstract: Image 1 Highlights: Graphene oxide (GO)/pyrrole-hyperbranched poly(amino ester) (HPPy) was prepared. GO/HPPy was first proposed to toughen biopolymer-based conductive film. Hyperbranched cross-linked structure was formed in the soy protein composites. Excellent conductive and mechanical properties of the film were achieved. Ultraviolet-barrier performance and water resistance of the films increased.